Abiotic niche partitioning and negative density dependence drive tree seedling survival in a tropical forest. Issue 1869 (13th December 2017) - Johnson, Daniel J.; Condit, Richard; Hubbell, Stephen P.; Comita, Liza S.
Abstract : In tropical tree communities, processes occurring during early life stages play a critical role in shaping forest composition and diversity through differences in species' performance. Predicting the future of tropical forests depends on a solid understanding of the drivers of seedling survival. At the same time, factors determining spatial and temporal patterns of seedling survival can play a large role in permitting species coexistence in diverse communities. Using long-term data on the survival of more than 45 000 seedlings of 238 species in a Neotropical forest, we assessed the relative importance of key abiotic and biotic neighbourhood variables thought to influence individual seedling survival and tested whether species vary significantly in their responses to these variables, consistent with niche differences. At the community level, seedling survival was significantly correlated with plant size, topographic habitat, neighbourhood densities of conspecific seedlings, conspecific and heterospecific trees and annual variation in water availability, in descending order of effect size. Additionally, we found significant variation among species in their sensitivity to light and water availability, as well as in their survival within different topographic habitats, indicating the potential for niche differentiation among species that could allow for species coexistence.